Transforming Growth Factor-Beta1 and Human Gingival Fibroblast-to-Myofibroblast Differentiation: Molecular and Morphological Modifications - Marconi, Guya D.; Fonticoli, Luigia; Rajan, Thangavelu Soundara; Lanuti, Paola; Della Rocca, Ylenia; Pierdomenico, Sante D.; Trubiani, Oriana; Pizzicannella, Jacopo; Diomede, Francesca (Frontiers in Physiology, 2021)
After oral mucosal injury, the healing response is initiated following specific steps that lead to the wound closure and to tissue repair. Multiple cell populations are involved in this process, in particular fibroblasts play a key role in the production of extracellular matrix (ECM). During wound heling the remodeling of ECM is a key stage to restore the tissue functionality through multifunctional fibroblast populations that are placed in the connective tissues of gingiva and periodontal ligament. Notably, a fibroblast sub-type (myofibroblast) is centrally involved in collagen synthesis and fibrillar remodeling. The present work evidenced the role of Transforming Growth Factor-beta1 (TGF-β1) to mediate human gingival fibroblasts (hGFs) differentiation into myofibroblasts derived from gingival fibroblasts (myo-hGFs). The morphological and functional features were analyzed through Confocal Laser Scanning Microscopy (CLSM), flow cytometry and western blotting analyses. The specific markers, such as alpha-Smooth Muscle Actin (α-SMA), Vimentin, E-cadherin, β-catenin and Smad 2/3 were modulated in myo-hGFs after the induction with TGF-β1, at different time points (24, 48 and 72h). After 72 hours of treatment TGF-β1 operates as an inducer of hGFs into myo-hGFs differentiation. We propose that TGF-β1 may promote in vitro the fibroblasts-to-myofibroblasts transition via the morphological and molecular modifications, as the induction of α-SMA, Vimentin, E-cadherin, β-catenin and Smad 2/3.